Uji Ketahanan dan Total Alkaloid Tembakau (Nicotiana tabaccum) Setelah Infeksi Ralstolnia solanacearum - Rofiatun Solekha; Putri Ayu Ika Setiyowati; Dimas Arya Nugraha; Karin Alifia Rachmadani (Program Studi Pendidikan Biologi, 2021)
Ralstolnia solanacearum is solanacearum is non forming, gram negative, aerobic plant pathogen that causes wilting in various host plant. Ralstolnia solanacearum is non these bacteria cause wilt disease in tabacco plants which can cause death by up to 50%. In tobacco plants, resistance analysis in the form of alkaloid content is required, the use of alkaloids in plants is as protection form pest attacks, plant reinforcements and hormone regulators. This study aims to analyze the resistance after developing tobacco wilt disease after Ralstolnia solanacearum infection. This study used kemloko 2 and kemloko 3 varieties as resistant treathments, kemloko 1 varieties which were susceptible to being used as negative controls, and moderately resistant Sindoro 1 varieties as positive controls. Reliability analysis using IP and AUDPC than the alkaloid cntent analysis using chloroform. The result showed the kemloko 3 variety tobacco had 103, 40 value; kemloko 2 11,74; sindoro 1 205,76; and kemloko 1 has value of AUDPC 350,22. Kemloko 3 is the most resistant variety after Ralstolnia solanacearum infection. The result of the analysis showed that the highest total alkaloid levels were found in kemloko 3, namely 15,760 ± 0,51 mg equivalent to the value of caffeine / gram. This shows that there is a correlation between the resistance of a plant to the many alkaloid compounds in the plant. The more resistant, the more lacloid compound content.